Galectin‐3–null mice display defective neutrophil clearance during acute inflammation. Issue 3 (12th October 2016) - Wright, Rachael D; Souza, Patricia R.; Flak, Magdalena B.; Thedchanamoorthy, Prasheetha; Norling, Lucy V.; Cooper, Dianne
Abstract : Expression of galectin‐3 by exudated neutrophils drives neutrophil apoptosis and clearance in a model of self‐resolving peritonitis. Abstract : Galectin‐3 has been associated with a plethora of proinflammatory functions because of its ability, among others, to promote neutrophil activation and because of the reduction in neutrophil recruitment in models of infection in Gal‐3‐null mice. Conversely, it has also been linked to resolution of inflammation through its actions as an opsonin and its ability to promote efferocytosis of apoptotic neutrophils. Using a self‐resolving model of peritonitis, we have addressed the modulation and role of Gal‐3 in acute inflammation. We have shown that Gal‐3 expression is increased in neutrophils that travel to the inflamed peritoneum and that cellular localization of this lectin is modulated during the course of the inflammatory response. Furthermore, neutrophil recruitment to the inflamed peritoneum is increased in Gal‐3–null mice during the course of the response, and that correlates with reduced numbers of monocytes/macrophages in the cavities of those mice, as well as reduced apoptosis and efferocytosis of Gal‐3–null neutrophils. These data indicate a role for endogenous Gal‐3 in neutrophil clearance during acute inflammation.